Randomized, Double-Blind, Placebo-Controlled Model Demonstrating a Local Effect of Benzydamine in Children with Tonsillopharyngitis - В.Р. Schachtel; D.A. Padjarino (Zaslavsky O.Yu., 2012)
Since there are few published randomized, double-blind, placebo-controlled studies that demonstrate the effectiveness of local anesthetic drugs in children, we have developed a method of clinical trials (involving 146 children with tonsillopharyngitis), determining the efficiency of the solution to rinse containing benzydamine, compared with placebo having the same appearance and taste. After a physical examination, including determination of the severity of tonsillopharyngitis and test for streptococci, there has been carried out an assessment of outcomes using «pain thermometer» for children and pain in throat scale for nurses before the child began randomly apply a solution for rinsing, containing the active drug or placebo. In regular intervals for 1 hour each child was examined by «pain thermometer» and pain relief in the throat scale for children -«smiley-face scale». The nurse carried out an independent assessment of changes of pain. We found that children and independent observations of nurses demonstrated a difference between the effect of the active drug and placebo (p < 0.05) on all three scales of assessment. We came to the conclusion that benzydamine relieves pain in tonsillopharyngitis. This clinical study can be used to identify the local anesthetic action of the drug in children with tonsillopharyngitis.